2023
DOI: 10.1177/09574565231154242
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of isolation performance of electric automobile seat’s suspension added by negative-stiffness structure models

Abstract: To evaluate the isolation performance of the negative-stiffness structure (NSS) used by the tuned-mass-damper (NSS-TMD) and the air pistons (NSS-AP) on improving the ride quality of the electrical automobile (EA), an EA’s dynamics model is built under the excitation of the road surface roughness and the in-wheel-motor. Based on the root mean square value of the driver’s seat acceleration response used to assess the driver’s ride quality, two models of the seat suspension added by NSS-AP and NSS-TMD are then si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The operation parameters in QSE-SS, QSE-RS, and QSE-AS had been also optimum to assess the isolation efficiency between QSE-SS, QSE-RS, and QSE-AS. 57 The results of the characteristics of the force-displacement and the value of RMS s of QSE-SS, QSE-RS, and QSE-AS were exhibited in the same Figure 20 and listed in Table 7. The investigations indicated that under the simulation condition, the characteristic of the force-displacement and value of RMS s with QSE-AS were lower than that of QSE-SS and QSE-RS.…”
Section: Development Of Seat Suspension Using Qsementioning
confidence: 79%
See 2 more Smart Citations
“…The operation parameters in QSE-SS, QSE-RS, and QSE-AS had been also optimum to assess the isolation efficiency between QSE-SS, QSE-RS, and QSE-AS. 57 The results of the characteristics of the force-displacement and the value of RMS s of QSE-SS, QSE-RS, and QSE-AS were exhibited in the same Figure 20 and listed in Table 7. The investigations indicated that under the simulation condition, the characteristic of the force-displacement and value of RMS s with QSE-AS were lower than that of QSE-SS and QSE-RS.…”
Section: Development Of Seat Suspension Using Qsementioning
confidence: 79%
“…Therefore, the riding quality of the driver was remarkably ameliorated by using QSE. In order to further enhance the QSE's isolation efficiency, based on the structure of QSE designed by steel springs (QSE-SS) in Figures 18 and 20a, these horizontal elastic springs were then replaced by using the rollersprings (QSE-RS) or air-pistons (QSE-AS), [54][55][56][57] as shown in Figures 20(b) and (c). The operation parameters in QSE-SS, QSE-RS, and QSE-AS had been also optimum to assess the isolation efficiency between QSE-SS, QSE-RS, and QSE-AS.…”
Section: Development Of Seat Suspension Using Qsementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the existing research also showed that a new structure of the quasi zero stiffness (QZS) designed and added into the driver's seat suspension could strongly improve the driver's ride comfort. [9][10][11][12] The experimental study of the QZS added into the seat's suspension to evaluate its actual isolation efficiency was also performed in Ref. [13] Then, the operation parameters of the QZS structure were optimized to enhance its efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…But this issue has not been considered yet. Besides, the vibration model of the vehicle seat's suspension equipped with the QZS structure was used by the vibration excitation of the rigid road surface to evaluate the isolation efficiency of the QZS structure, [10][11][12][13][14] the soil compactors mainly moved and compressed on the elastoplastic terrains. Therefore, the QZS structure also needs to be evaluated under the excitation of the deformable terrain surface to evaluate its isolation efficiency and stability.…”
Section: Introductionmentioning
confidence: 99%